The politics of transformation in South Africa: an evaluation of education policies and their implementation with particular reference to the Eastern Cape Province - Rembe, Symphorosa Wilibald (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2006)
The post-apartheid government of South Africa has committed itself to achieving fundamental transformation of the education system. The government has adopted policies and measures that aimed to bring about the goals of equity and redress, and to enhance democracy and participation of all groups in development and decision making processes at all levels. It is acknowledged that the democratic government has accomplished a lot in education within this short period and has made numerous strides in enhancing equity, redress and social justice; providing high quality education for all the people of South Africa; bringing about democratisation and development; and enhancing effectiveness and efficiency. However, despite these apparent achievements, this study shows that there have been a number of setbacks and contradictions in the policies which have affected the process of bringing about fundamental changes and transformation in the education sector. The setbacks and contradictions resulted from factors which have affected the type of policies developed to transform the education sector. They also affected the formulation and implementation of the policies, thereby limiting the achievements of the goals of transformation agenda in education. Hence, this study examined the politics of transformation and change in the education sector by examining the type of policies that have been put in place; their formulation, implementation and outcome. The main research questions are: "¢ What kind or type of policies have been put in place to transform the education sector? "¢ How and by whom were the policies formulated? "¢ How are these policies being implemented and what have been the outcomes of the process? Transformation and in particular the policy process is beset with continuous debate, contestation and struggle for the success of ideas and interests which are pursued by individual actors, groups and policy networks through the institutions. During these different stages policies are modified, constituted and reconstituted. As a result, they give rise to intended and unintended outcomes which are likely to support or contradict the objectives of those policies. Hence, the process cannot be explained using only one approach or theory. Therefore, this study has been situated in ideas, group and network and institutional approaches or theories to examine the factors that have affected education policies, their formulation and implementation and the overall transformation of education in South Africa. It contends that policy change and variation result from interaction of ideas and interests within patterns of group and policy networks and preset institutions. The study adopts qualitative interpretive methodology in order to question, understand and explain institutions; interests groups and ideas; socio economic and power relations involved in the process. It also appraises the framework for action. In addition to conducting literature review, unstructured interviews were held with officials from provincial and national Departments of Education, members of national and provincial legislatures, principals, teachers, members of school governing bodies, learners, Non-governmental organisations, Community based organisations, Faith based organisations, teachers' and workers' unions. Observations were made during meetings of school governing bodies. The study draws reference from the Eastern Cape Province between 1994 and 2002 and looks at the school level (Basic and Further Education levels). Reference is also made to selective policy instruments namely, the South African Schools Act (SASA) (1996), Curriculum 2005 and Norms and Standards for School Funding (1999). Overall, the findings of the study have shown that various factors have led to setbacks and contradictions in the policies that were adopted in education. They have also affected the formulation and implementation of the policies, hence exerting certain limitations on the achievements of the goals of transformation in education. The factors identified in the findings are the outcome of the negotiated settlement and subsequent changes made by the apartheid government in education before the 1994 elections; constraints and unequal participation of different groups in education policy development in various established structures and avenues; drawbacks in the implementation of education policies by decentralised structures and agents at various levels. This was exacerbated by lack of capacity, lack of adequate resources, lack of commitment and will among some of the civil servants coupled with corruption and mismanagement. The legacy of apartheid and the homeland governments, together with existing backlogs added another layer. Consequently, there were challenges in the economic policy which led to inadequate funding for education. The findings of this study show that competing ideas and interests advanced by groups and networks have impact on decision making, policy content and implementation. Therefore, some policies will reflect and maintain the interests of those individual actors, groups and policy networks that exerted most influence. The findings also reveal that institutional norms and rules, inadequate resources, lack of capacity and skilled human resources and economic environment, constrain decision making, policy content and implementation.
Keywords: Educational change -- South Africa -- Eastern Cape; Education -- Political aspects -- South Africa -- Eastern Cape; Education and state -- South Africa -- Eastern Cape; Post-apartheid era -- South Africa; South Africa -- Politics and government -- 1994-